How truthful is Chief Seattle's famous conservation-oriented speech? - Hilje, Luko (2021)
The legitimacy of a touching conservation-oriented speech attributed to Chief Seattle, dating from 1854, has been debated for many years. Nevertheless, it was written in 1970 for the television series Home by screenwriter Ted Perry, inspired by a speech by Chief Seattle which was reconstructed and published by Henry A. Smith in 1887. To dispel any doubt about the exact content and paternity of such a controversial text, the versions of Smith and Perry are included here —translated into Spanish by the same person, to avoid any bias—, and they are placed in the historical context in which they appeared.